(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
In this research work, the authors introduce a new tool namely the dual-test model of antecedents that need to be standardized to objectively assess the skills of offensive volleyball plays and young athletes between the ages 12 and 16 years. Valid and reliable testing in competitive sports is necessary in the determination of future talent in competitive sports, which requires organized long-term improvement in competition. Using a quantitative cross-sectional research study, the sample size consisted of 140 participants involving youth volleyball players stratified by age and gender. Balancing of participants was applied by stratifying random selection of young volleyball participants in clubs and academies. The physical and the offensive skill battery will be combined into two sections that will form the proposed model; (A) A physical test battery which will assess explosive power, speed, agility, strength, and coordination using tests such as vertical jump, sprint, agility test, long jump and grip strength; (B) The offensive skills battery that will examine serve accuracy, spike performance, setting accuracy and in optional circumstances, offensive decision-making. The test was carried out in a pilot study with 20 athletes to iron out unclarity and timing in tests. The psychometric features of the model were extensively confirmed with test-retest (ICC > 0.85), inter-rater (Cohen Kappa > 0.80) and construct and content validity through coach rankings and expert panels. All subtests were put into a z-score form, which fed into two indices called Physical Index (PI) and Offensive Skills Index (OSI), which united to create a Total Talent Index (TTI) with regression weights based on coach ratings. The TTI had an excellent predictive value regarding coach rated talent (R 2 > 0.70). The gap between different age groups and gender highlights a particular need of context grounded benchmarks. The dual-test model provides a scalable, standardisable system that can be used in identifying volleyball talent among youth, and would be appropriate to incorporate within national development pathways and longitudinal monitoring.